Bench to Bedside: Stability Studies of GMP Produced Trastuzumab-TCMC in Support of a Clinical Trial - Diane E. Milenic; Kwamena E. Baidoo; Martin W. Brechbiel (MDPI AG, 2015)
The first-in-human phase 1 clinical radioimmunotherapy (RIT) trial with 212Pb-1,4,7,10-tetraaza-1,4,7,10-tetra-(2-carbamoylmethyl)-cyclododecane-trastuzumab (212Pb-TCMC-trastuzumab) was completed in October 2014 as a joint effort at the University of Alabama (UAB) and the University of California San Diego Moores Cancer Center. The preliminary reports indicate that after five dose-levels of intraperitoneally administered 212Pb-TCMC-trastuzumab, patients with carcinomatosis experienced minimal agent-related toxicity. This report presents the data accumulated to date on the stability of the clinical grade, produced according to current good manufacturing practices (cGMP), TCMC-trastuzumab conducted in support of that clinical trial. Of the eleven tests performed with the cGMP TCMC-trastuzumab all but one remained within specifications throughout the 5 year testing period. The protein concentration varied by 0.01 mg/mL at 48 months. Two other assays, ion-exchange high performance liquid chromatography (IEX-HPLC) and a competitive radioimmunoassay (RIA) indicated that the cGMP TCMC-trastuzumab integrity may be changing, although the change thus far is within specifications. Subsequent stability testing will confirm if a trend has truly developed. The cGMP TCMC-trastuzumab was also evaluated for tolerance to higher temperatures and the potential of storage at −80 °C. The immunoconjugate proved stable when subjected to the lower temperatures and to multiple freeze-thaw cycles. The size exclusion (SE) HPLC analysis of the 203Pb-TCMC-trastuzumab was the only indicator that cGMP TCMC-trastuzumab may be sensitive to storage at 37 °C for 3 months.